Fascial plane blocks: a narrative review of the literature. Issue 7 (18th June 2021) - Kim, David H; Kim, Sang Jo; Liu, Jiabin; Beathe, Jonathan; Memtsoudis, Stavros G
Abstract : Fascial plane blocks (FPBs) are increasingly numerous and are often touted as effective solutions to many perioperative challenges facing anesthesiologists. As 'new' FPBs are being described, questions regarding their effectiveness remain unanswered as appropriate studies are lacking and publications are often limited to case discussions or technical reports. It is often unclear if newly named FPBs truly represent a novel intervention with new indications, or if these new publications describe mere ultrasound facilitated modifications of existing techniques. Here, we present broad concepts and potential mechanisms of FPB. In addition, we discuss major FPBs of (1) the extremities (2) the posterior torso and (3) the anterior torso. The characteristics, indications and a brief summary of the literature on these blocks is included. Finally, we provide an estimate of the overall level of evidence currently supporting individual approaches as FPBs continue to rapidly evolve.